(untitled) (Research, Society and Development, 2022)
Eucalyptus radiata is a plant species native to Australia, ecologically important and a source of essential oils (EO) with potential biological activities such as anti-inflammatory, antioxidant, analgesic, fatigue-reducing, hypoglycemic, insecticidal and bactericidal action, which are generally attributed to the present biochemical composition. in the EO, mainly to the marjoritarian compound 1,8-cineole. However, there are no studies investigating the possible healing potential of E. radiata EO, which makes this plant an important target for new therapeutic formulations. Thus, the present study aimed to characterize the healing effect of E. radiata EO in dermatological wounds. For this purpose, a topical cream was prepared with E. radiata EO, which was subjected to physicochemical characterization and in vivo analysis (Wistar albinus). As a result, it can be seen that the cream made with the EO of E. radiata (1.5, 3.5 and 5%) presented a homogeneous aspect characteristic of an emulsion oily/aqueous phase, without the presence of lumps, it did not present significant changes in the appearance, color and odor, in terms of pH (3.82 - 3.90) and density, there were no great variations between the formulations. Therefore, the use of E. radiata EO in the formulation of a cream proved to be viable, maintaining the characteristic odor of the oil, adequate spreadability, no color change, keeping its stability constant in most of the tests performed. The cream gel based on 5% of E. radiata EO, in this work, demonstrated the potential to stimulate and favor the healing process in vivo in Wistar allbinus rats.